As santinhas de casa que fazem milagres: devoções à Mariazinha Penna (Santa Maria) e à Maria Elizabeth de Oliveira (Passo Fundo) - Cassol, Francielle Moreira (2021)
Maria Zaira Cordova Penna, better known in the central region of the state of Rio Grande do Sul as Mariazinha, died at the age of twenty in 1953, a victim of painful femur cancer. Maria Elizabeth de Oliveira, a fourteen-year-old girl from Passo Fundo who was the victim of a car accident, had predicted her death, choosing her coffin days before the accident in 1965. The life stories and what happened after their deaths are today a source of intense devotion and emotion in the cemeteries of the cities where they are buried, in Santa Maria and Passo Fundo/RS. The two young women are immortalized in the memories and hearts of those who believe in them. Today, Mariazinha and Maria Elizabeth are two of the greatest exponents of popular devotion in the interior of the state. In view of this, this paper seeks to analyze the creation and development of the two devotions, as well as the consolidation of the founding discourses of the saints in the bibliographic ex-votos: hagiographies as a vector of gratitude and belief. To this end, it is based on the historiographical current known as Cultural History; as well as, methodologically, Regional History. Regarding the research sources, the work is based on biographical books, journalistic sources and memory notebooks, which were left on the tombs and filled by the faithful with their memories and requests.